Biomechanical load during patient transfer with assistive devices: Cross-sectional study. Issue 9 (1st September 2020) - Vinstrup, Jonas; Jakobsen, Markus D.; Madeleine, Pascal; Andersen, Lars L.
Abstract: This study utilised a cross-sectional design to perform measurements of muscle activity as well as forward - and lateral trunk inclination angle during a full workday among 52 female healthcare workers from 16 different departments at five Danish hospitals. Using linear mixed models, the 95th percentile ranks of the normalised root mean square (nRMS) values were analysed for the different types of assistive devices. Compared to no assistive device (mean nRMS 27.9%, 95% CI 24.8%–31.0%), the use of intelligent beds (23.9%, CI 20.2%–27.6%) and ceiling-lifts (24.0%, CI 20.3%–27.7%) led to lower erector spinae nRMS values across all types of patient transfers. Conversely, the use of bedsheets (30.6%, CI 27.1%–34.2%), sliding-sheets (30.3%, CI 26.8%–33.9%) and sliding-boards (33.5%, CI 29.5%–37.6%) were associated with higher levels of erector spinae muscle activity. Consistent use of ceiling-lifts and intelligent beds reduces the physical workload and may thereby decrease the risk of musculoskeletal disorders among healthcare workers. Practioner Summary: Frequent patient transfer is associated with an increased risk of back pain and injury among healthcare workers. This analysis compares the level of physical load during patient transfer with commonly used assistive devices. The results show that use of the ceiling-lift and intelligent bed is associated with relatively low physical load during patient transfer. Abbreviations: RMS: root mean square; nRMS: normalized root mean square; EMG: electromyography; MSD: musculoskeletal disorder; LBP: low-back pain; VAS: visual analogue scale; MVC: maximal voluntary contraction